Surviving the age of virtual reality - Langan, Thomas (University of Missouri Press, 2000)
As the technological phenomenon known as the worldwide web permeates civilization, it creates some cultures and destroys others. In this pioneering book, philosopher Thomas Langan explores "virtual reality"Can inherently contradictory phrase"and the effects of technology on our very being. In our present-day high- technology environment, making simple, everyday decisions is difficult because the virtual world we've created doesn't necessarily operate according to the old "common sense." To retain our intellectual fitness, we must, Langan argues, consider these essential questions: If virtual reality is, in fact, reality, what is this life that we are caught up in? What is being within the context of virtual reality? How can we establish a system for distinguishing truth from fiction? Although technology minimizes distances between people and makes the information they seek more accessible, it simultaneously blurs the line dividing fact from falsehood and real from virtual. An individual's intellectual survival is threatened as technological advancement challenges our collective understanding of what reality is. Because much of the information that is presented as fact simply works to fulfill a specific agenda, we cannot accept as truth everything that appears on the internet or in the media. To survive, we must learn to manage our lives and resources despite the flood of information we are bombarded with daily. Addressing the general educated reader, Surviving the Age of Virtual Reality expertly interweaves the worlds of technology and philosophy, pushing the analysis of this technological and human phenomenon to new depths